A Most Eminent Victorian: Thomas Henry Huxley - Sherrie Lyons (Cahiers Victoriens et Edouardiens)
Huxley coined the word agnostic to describe his own philosophical framework in part to distinguish himself from materialists, atheists, and positivists. In this paper I will elaborate on exactly what Huxley meant by agnosticism by discussing his views on the distinctions he drew between philosophy and science, science and theology, and between theology and religion. His claim that theology belonged to the realm of the intellect while religion belonged to the realm of feeling served as an important strategy in his defense of evolution. Approaching Darwin’s theory in the spirit of Goethe’s Thatige Skepsis or active skepticism, he showed that most of the “scientific” objections to evolution were at their root religiously based. Huxley maintained that the question of “man’s place in nature” should be approached independently of the question of origins, yet at the same time argued passionately and eloquently that even if humans shared a common a origin with the apes, this did not make humans any less special. Because evolution was so intertwined with the questions of belief, of morals and of ethics, and Huxley was the foremost defender of Darwin’s ideas in the English-speaking world, he was at the center of the discussions as Victorians struggled with trying to reconcile the growing gulf between science and faith.